2009
DOI: 10.1111/j.1469-7610.2009.02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological vulnerability in children next‐born after stillbirth: a case–control follow‐up study

Abstract: This study provides no evidence to suggest that siblings born after stillbirth are clinically at risk but does lend empirical support to clinical reports that such children are seen by their mothers as having problems and that they are exposed to less optimal interaction with their mothers. Possible interpretations of these findings are discussed in the context of theoretical accounts of 'replacement child' and 'vulnerable child' syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…Stillbirth has been described as a paradoxical coalescence of life and death, 3 and the trauma of this experience is associated with increased incidence of anxiety, depression and post-traumatic stress disorder. [4][5][6] Owing to the social stigma associated with stillbirth, 7 it is an isolating event leaving mothers more dependent on their own psychological and emotional resources and on those that care for them. 3 The burden on staff is demonstrated internationally in studies of maternity professionals who report that caring for families experiencing a stillbirth is a stressful aspect of their work.…”
Section: Introductionmentioning
confidence: 99%
“…Stillbirth has been described as a paradoxical coalescence of life and death, 3 and the trauma of this experience is associated with increased incidence of anxiety, depression and post-traumatic stress disorder. [4][5][6] Owing to the social stigma associated with stillbirth, 7 it is an isolating event leaving mothers more dependent on their own psychological and emotional resources and on those that care for them. 3 The burden on staff is demonstrated internationally in studies of maternity professionals who report that caring for families experiencing a stillbirth is a stressful aspect of their work.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51] Methods to document GBS-related stillbirths that can be implemented in high-income as well as in middle-and low-income countries should be codified to enhance comparisons between studies. For instance, the Brighton Collaboration and the WHO are currently collaborating on consolidating definitions of stillbirth to prevent any variation in definition.…”
Section: Resultsmentioning
confidence: 99%
“…Since prenatal attachment has been significantly correlated with postpartum bonding [15], it is reasonable to expect that women with a history of perinatal loss may have an increased risk of impaired maternal-infant bonding. Evidence also exists that women with a history of perinatal loss are more concerned with the health of their child [16,17] and report more problems with their child both in early infancy [18] and at school age [19]. However, Price [20] found no difference in the way mothers with a history of perinatal loss interacted with or perceived the behavior of their infants born subsequent to perinatal loss.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of mothers of children born subsequent to stillbirth, Turton and colleagues [19] found that although mothers with a history of stillbirth reported that their children had more difficulties and peer problems than was reported by a control group of mothers, teacher ratings did not show any difference. This suggests that a relationship issue between the child and the mother may exist even when the child is otherwise perceived by others as functioning normally.…”
Section: Introductionmentioning
confidence: 99%